Overview of pregnant women's knowledge in the thirty trimester about exclusive breastfeeding at the Bertha Mabar Hilir Pratama Clinic in 2024 - Veronika, Anita; Kristina, Elsa; Manik, Risda Mariana; Ginting, Agustaria (Institute of Computer Science (IOCS), 2024)
Exclusive breastfeeding is the process of providing only breast milk to babies from 0-6 months of age without additional food such as formula milk. After 6 months, babies need additional food (MP-ASI) to meet the needs of minerals and other nutrients such as iron. The impact of not exclusive breastfeeding for babies is diarrhea, pneumonia, obesity, decreased immunity, stunting and malnutrition, and the impact of not breastfeeding for mothers is death from breast cancer, ovarian cancer and type II diabetes. The purpose of the study was to determine the description of the knowledge of pregnant women in the third trimester about exclusive breastfeeding at the Bertha Mabar Hilir Pratama Clinic in 2024. Research method: descriptive using a cross-sectional design. Sample: 50 respondents of pregnant women in the third trimester. Sampling technique: total sampling. Results: The results of the study showed that the knowledge of mothers was mostly sufficient, namely 30 respondents (60%), 11 respondents (22%) had good knowledge and 9 respondents (18%) had less knowledge. Suggestion: The researcher suggests that mothers who have poor knowledge to improve their knowledge, especially about Exclusive Breastfeeding, by obtaining information from various sources such as health workers and mass media, those who are busy with their work can also access information about Exclusive Breastfeeding from social media so that it is easier, especially for primiparous mothers who have not had the experience of giving birth, so that the mother's knowledge becomes good and preparation for breastfeeding during the antenatal period can be fulfilled and when they have given birth, they are expected to be able to provide Exclusive Breastfeeding to their children.